2018
DOI: 10.1002/1873-3468.13245
|View full text |Cite
|
Sign up to set email alerts
|

The role of chaperones in iron–sulfur cluster biogenesis

Abstract: Iron-sulfur cluster biogenesis is a complex process mediated by numerous proteins among which two from bacteria chaperones, called HscB and HscA in bacteria. They are highly conserved up to eukaryotes and homologous to DnaJ and DnaK, respectively, but with specific differences. As compared with other chaperones, HscB and HscA have escaped attention and relatively little is known about their functions. After briefly introducing the various chaperone families, we reviewed here the current structural and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…HscB and TGF‐β3 are highly differentially expressed proteins in chaperone binding and transforming growth factor beta binding, respectively (Figure 4B). HscB acts as a cochaperone of Hsp70 and mediates iron‐sulfur cluster biogenesis 38 . It has been reported that highly expressed TGF‐β3 is tightly linked to PCa suppression 39 .…”
Section: Resultsmentioning
confidence: 99%
“…HscB and TGF‐β3 are highly differentially expressed proteins in chaperone binding and transforming growth factor beta binding, respectively (Figure 4B). HscB acts as a cochaperone of Hsp70 and mediates iron‐sulfur cluster biogenesis 38 . It has been reported that highly expressed TGF‐β3 is tightly linked to PCa suppression 39 .…”
Section: Resultsmentioning
confidence: 99%
“…HscAs seem to be highly specialized to chaperoning the transfer of Fe-S-clusters from IscU to an apo-enzyme in cooperation with the JDP HscB [for review see ( Puglisi and Pastore, 2018 )]. Whereas HscAs are only found in bacteria, HscB homologs also exist in mitochondria where they either interact with the generalist DnaK-type Hsp70 (in most eukaryotic cells) or with a specialized Hsp70 (some fungi) that emerged by convergent evolution but is still more DnaK-like than HscA-like ( Schilke et al, 2006 ; Kleczewska et al, 2020 ).…”
Section: Hsca and Hscc: Variations Of The Themementioning
confidence: 99%
“…The highest expression of these proteins was observed at the beginning of the process when the mcl-PHAs started to be produced. DnaK is involved both in co-and post-translational folding processes, whereas HscA seems to be specialized for the assembly of iron-sulfur cluster proteins [32,33]. Genetic studies indicated that the deletion of the dnaK and hscA genes revealed that they are not absolutely essential for bacterial survival.…”
Section: Stress Responsementioning
confidence: 99%